2020
DOI: 10.1186/s40814-020-00581-6
|View full text |Cite
|
Sign up to set email alerts
|

Development and feasibility of an intervention featuring individual supported work placements to aid return to work for unemployed people living with chronic pain

Abstract: Background: Working in good jobs is associated with good health. High unemployment rates are reported in those disabled with musculoskeletal pain. Supported employment interventions work well for helping people with mental health difficulties to gain and retain employment. With adaptation, these may be useful for people with chronic pain. We aimed to develop and explore the feasibility of delivering such an adapted intervention. Methods:We developed an intervention and recruited unemployed people with chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Despite testing a range of different methods in primary care, recruitment of individuals unemployed with chronic pain proved challenging and resource-intensive. Consequently, and in accord with the findings of another UK study (Froud et al, 2020), we have shown that, at least in the UK, a definitive trial would currently not be feasible with the major barrier being the lack of a whole systems approach to health and employment. If appropriate employment support is to be made available to people with pain, there is an urgent need for accurate and up-to-date employment status to be held in primary care records and to improve ability to link health and work data for the future.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Despite testing a range of different methods in primary care, recruitment of individuals unemployed with chronic pain proved challenging and resource-intensive. Consequently, and in accord with the findings of another UK study (Froud et al, 2020), we have shown that, at least in the UK, a definitive trial would currently not be feasible with the major barrier being the lack of a whole systems approach to health and employment. If appropriate employment support is to be made available to people with pain, there is an urgent need for accurate and up-to-date employment status to be held in primary care records and to improve ability to link health and work data for the future.…”
Section: Discussionsupporting
confidence: 80%
“…Either way, as was suggested in our qualitative work with people with chronic pain (Holmes et al, 2020), follow-up over 12 months may be too soon to fully appreciate the effectiveness of IPS on return to work in a trial, and assessment of employment status at 24 months or longer may be a more appropriate primary outcome, as used by Hellstrom and co-workers in their study of IPS in people with mood and anxiety disorders (Hellstrom et al, 2017). We experienced difficulty in obtaining responses to follow-up questionnaires (40% non-receipt) despite incentives and reminders, with rates of attrition similar to those seen in a similar study (Froud et al, 2020). Interestingly, in a study of IPS amongst people with moderately severe mental ill-health, only a 60% response to questionnaires was anticipated (Reme et al, 2019).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The review was part of a larger study (Return to work with Individualised Supported Employment -RISE), which was funded by Versus Arthritis, and was designed to determine the feasibility of delivering an individualised supported work placement intervention to people with chronic pain. The early phases of the present review informed the intervention development process and the choice of outcome measures used in the RISE intervention (Froud et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…We recommend future trialists consider defining primary outcomes as sustained return to competitive employment within a specified time period, which may better align with real-world aims (Jensen et al, 2012). Further, this may allow time needed for secondary impacts on quality of life to be realised (Froud et al, 2020). That said, we note that quality of life was not included in most trials' measurement of non-vocational outcomes.…”
Section: Main Findings and Implicationsmentioning
confidence: 99%